Immunological studies in patients with chronic renal failure (Colombia Medica, 1982)
Patients with chronic renal failure (CRF) under maintenance hemodialysis were compared with a group of healthy controls concerning the following immunological parameters: T, B, and null lymphocyte values, serum IgG, IgM, and IgA, total hemolytic complement (CH50) and skin reactivity to dinithrochlorobenzene (DNCB) sensitization. Patients with CRF showed decreased numbers and percentages of B lymphocytes (surface immunoglobulin positive cells, sIg +) as measured by direct immunofluorescence. Most of the patients exhibited cutaneous anergy to DNCB.